Abstract This study examines the impact of teachers’ pedagogical competence on students’ religious attitudes in Islamic Religious Education learning. Adopting a mixed-methods approach, data were collected through questionnaires, classroom observations, an - SOIM (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2026)
This study examines the integration of Islamic Religious Education (IRE) and character education as a multidimensional approach to strengthening students’ moral values in secondary schools. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews with teachers, and document analysis. The findings indicate that integrating religious teachings with character-based pedagogy fosters moral internalization, ethical awareness, and responsible behavior among students. The integration is most effective when supported by contextual learning, teacher role modeling, and school culture. This study contributes to the discourse on moral education by offering an integrative framework that aligns religious instruction with contemporary character education goals. The findings have implications for curriculum development and teacher professional training in Islamic education contexts..